The Fund's Mandate-The Legal Framework. (Policy Papers; Policy Paper ;, 2010)
This paper is intended to accompany 'The Fund's Role and Mandate-An Overview' (the 'Mandate Overview Paper'). Taking into account the issues raised in the Mandate Overview Paper and, in particular, the potential areas for reform that it identifies, this paper provides a brief analysis of both the constraints and flexibility that exist under the existing legal framework. At the outset, it is useful to identify several aspects of this framework that are of particular relevance.